Assessment of oral health status of old age home residents and community dwelling older adults and its association with depression in Eastern Nepal: A comparative cross-sectional analytical study - Gautam, Ujwal; Bhagat, Tarakant; Baral, Dharanidhar; Nepal, Suraj (Journal of Karnali Academy of Health Sciences, 2025)
Background: Changing family practice has led to increased number of ageing population in old age homes. Multiple factors have a role in deteriorating oral health of older adults. The study assesses and compares oral health status in old-age home residents of eastern Nepal with community dwelling counterparts and look into its association with depression.Data and Methods: A cross-sectional comparative analytical study was conducted among 42 older adults from old age homes and community each. Old age home residents were selected using multistage random sampling while community dwelling older adults were selected using systematic random sampling after matching for age and sex. Structured questionnaires were used to interview participants on oral health behaviour and depression. Oral examination was conducted to assess plaque control, caries outcome andperiodontal status. Oral health outcomes were compared across two population using inferential statistics like chi-square test, or Mann Whitney U test. Logistic regression was conducted to explore how oral health outcome variables were influenced by depression and other covariates.Results: Of the total participants, four were edentulous. About 63.8% of the participants had periodontitis while 45.2% had less than 20 remaining teeth. DMFT (Decayed, Missing, Filled Teeth) scores and prevalence of periodontitis were significantly higher in old age home residents; median DMFT [17.5 (Range: 0-32); p=0.014) and periodontitis [37.5%; p=0.036)] respectively. Depression, after adjusting for other covariates, was significantly associated with periodontitis (OR: 7.124; CI: 1.310-38.730) and number of remaining teeth (OR: 0.11; CI: 0.011-0.497).Conclusion: The older adults in this study had poor oral health status. Significant difference exists in the oral health status outcome between old-age home residents and community dwelling older adults. Moreover, depression is found to be associated with oral health outcomes. It is worthwhile to assess the factors behind the disparity in oral health status between old age residents and community dwelling older adults.